Perlawanan Masyarakat Samin (Sedulur Sikep) Atas Kebijakan Pembangunan Semen Gresik Di Sukolilo Pati (Studi Kebijakan Berbasis Lingkungan Dan Kearifan Lokal) - Subarkah .; Anggit wicaksono (LPPM Universitas Pekalongan, 2014)
Pluralistic society is a rich culture that is always maintained and preserved in which there are values, and norms prevailing in the society, therefore the increased pace of development, any development planning where customs values, norms, culture, who have local knowledge (local wisdom) need to be taken into account by looking at a holistic approach to the environment. Issues that arise in the district Sukolilo Pati, the Samin community or Sedulur resistance against the construction of Semen Gresik Sikep is very interesting to study or do research more deeply both doctrinal and non-doctrinal. This study used a Constructivist paradigm , which views law as the law as relative and contextual consensus ( law on hakektnya an agreement , whether written mapun unwritten are relative and contextual ) approach socio legal studies legal problems are not merely conceived as the norm and simultaneously interpret the law as behavior . Local knowledge is a form of appreciation of humanity and as a servant of God in the process of social interaction , not only with our fellow human beings , but also to the environment . Sikep Sedulur understanding of the environment that have so far not included a simple lifestyle change that has been handed down , including ecological balance is maintained and well preserved with two (2 ) aspects: Aspect and Aspect Emperik transcendental . Samin community of resistance to the paradigm associated with environmental and healthy good life in accordance with local knowledge . Language of